Effect of acupuncture on neuroinflammatory responses in depression animals: a systematic review and meta-analysis - Ni, Dongyi; Zhang, Jinbu; Qi, Ruyu; Huang, Yingjie; Li, Min; Duan, Lining (Frontiers in Psychiatry, 2025)
BackgroundDepression causes many negative effects and even death to patients; the burden on society is also heavy in terms of economics. The neuroinflammatory mechanism of acupuncture regulating depression is unclear. Thus, this study evaluated the effect of acupuncture on neuroinflammatory responses in depression animals and provided a clinical reference for depression treatment.MethodsThe Web of Science, Embase, the Cochrane Library, PubMed, CNKI, WanFang, CBM, and VIP databases were searched. The SYRCLE Risk of Bias Tool was used to assess bias in the studies. Meta-analysis was performed using Stata 15.0. The sources of heterogeneity were explored using subgroup analysis, and stability was evaluated using sensitivity analysis. Quality of evidence for outcomes was assessed using GDT.ResultsThis study included 25 studies and 466 animals. According to meta-analysis, compared with the control group, acupuncture significantly reduced IL-1β (SMD: −1.62, 95% CI: −1.93, −1.31), IL-6 (SMD: −1.89, 95% CI: −2.51, −1.26), and TNF-α in depression animals (SMD: −2.09, 95% CI: −2.83, −1.34) and improved IL-4 (SMD: 1.01, 95% CI:0.35, 1.67), IL-10 (SMD:0.77, 95% CI:0.26, 1.28), body weight (SMD:1.69, 95% CI: 1.23, 2.15), crossing numbers (SMD: 1.74, 95% CI: 1.31, 2.17), and rearing numbers (SMD: 1.77, 95% CI: 1.16, 2.39).ConclusionAcupuncture has the potential to alleviate depression by attenuating neuroinflammatory responses, and the mechanism may be related to modulating the release of inflammatory factors as well as regulating the activation of microglia.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024534237.